1997
DOI: 10.1115/1.2815532
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting NOx Formation in Lean-Premixed Combustion

Abstract: The formation of NOx in lean-premixed, high-intensity combustion is examined as a function of several of the relevant variables. The variables are the combustion temperature and pressure, fuel type, combustion zone residence time, mixture inlet temperature, reactor surface-to-volume ratio, and inlet jet size. The effects of these variables are examined by using jet-stirred reactors and chemical reactor modeling. The atmospheric pressure experiments have been completed and are fully reported. The results cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…when z = 2.5 ms. Also, as seen in Fig. 10, our measured values of NO emissions were in close agreement with propane-air data of Steele et. al.…”
Section: )supporting
confidence: 91%
“…when z = 2.5 ms. Also, as seen in Fig. 10, our measured values of NO emissions were in close agreement with propane-air data of Steele et. al.…”
Section: )supporting
confidence: 91%
“…For the first positive system, a 600 grooves/mm grating and a longpass interference filter absorbing light for  < 420 nm were used. The emission of the N 2 (CB) (0,2) and (1,3) vibrational bands were recorded around 380 nm, and that of N 2 (BA) (3,0) to (11,8) between 610 and 710 nm. Absolute intensity calibration was done with a tungsten radiance standard (OL 550) keeping all parameters identical.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Nevertheless, when Rutar [13] studied NO x and CO emissions at an elevated pressure of 3.0-6.5 atm he concluded that NO x decreased a little with increasing pressure for a fixed residence time, which was also revealed by Steele et al [14]. Biagioli and Güthe [15] analyzed the NO from 1-30 bar based on a model, and they found that the NO x pressure exponent is negative under fully premixed conditions.…”
Section: Introductionmentioning
confidence: 84%
“…From Equation (14), one can clearly see the influence of P and ṁF/ṁpri on tg, tg decreased with an increase in P (P −0.43 ), but increased significantly with the increasing of ṁF/ṁpri ((ṁF/ṁpri) 2.07 ). A comparison of the measurement and prediction of tg with correlation Equation 14is presented in Figure 11.…”
Section: Global Flame Residence Timementioning
confidence: 99%